2021
DOI: 10.3390/biom11091360
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-Neurotrophin Interactions in Heart, Retina, and Brain

Abstract: Ischemic insults to the heart and brain, i.e., myocardial and cerebral infarction, respectively, are amongst the leading causes of death worldwide. While there are therapeutic options to allow reperfusion of ischemic myocardial and brain tissue by reopening obstructed vessels, mitigating primary tissue damage, post-infarction inflammation and tissue remodeling can lead to secondary tissue damage. Similarly, ischemia in retinal tissue is the driving force in the progression of neovascular eye diseases such as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 299 publications
(474 reference statements)
0
17
0
1
Order By: Relevance
“…We have recently demonstrated that expression of the neurotrophin Ngf is dependent upon TGFβ2 treatment in vitro and is significantly enhanced in the juvenile retina of a mouse model with increased TGFβ signaling activity [ 12 ]. Hence, the fact that ‘p75 neurotrophin receptor’ was amongst the genes that were upregulated in VPP but not regulated in double mutant retinae might point towards an interaction of neurotrophin and TGFβ signaling, as postulated in previously published manuscripts from our group [ 12 , 34 ] and others [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We have recently demonstrated that expression of the neurotrophin Ngf is dependent upon TGFβ2 treatment in vitro and is significantly enhanced in the juvenile retina of a mouse model with increased TGFβ signaling activity [ 12 ]. Hence, the fact that ‘p75 neurotrophin receptor’ was amongst the genes that were upregulated in VPP but not regulated in double mutant retinae might point towards an interaction of neurotrophin and TGFβ signaling, as postulated in previously published manuscripts from our group [ 12 , 34 ] and others [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 72%
“…TGFβ signaling has a plethora of different functions such as cell-cycle control, cell differentiation, and regulation of early development [ 31 , 32 , 33 , 34 ]. As the Cre recombinase in Tgfbr2 ΔOC retinae is constitutively expressed from embryonic day 10.5 in all cells deriving from the inner layer of the optic cup e.g., retinal neurons and Müller cells [ 35 ], we addressed potential developmental-related aspects in the Tgfbr2 ΔOC model in one of our previously published manuscripts [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the molecular interactions of BDNF and NGF in the diabetic retina have shown that both molecules exhibit pro-angiogenic effects and contribute to the formation of neovascularization in proliferative diabetic retinopathy [ 176 ]. This is either directly, by binding to Trk receptors on endothelial cells, or indirectly, by promoting vascular endothelial growth factor (VEGF) expression in other cells [ 177 , 181 , 182 , 183 , 184 , 185 , 186 ]. Thus, inhibition of VEGF by intravitreal injection of bevacizumab, a humanized anti-VEGF monoclonal antibody commonly used to inhibit neovascularization in patients with proliferative diabetic retinopathy, results in marked reduction of retinal NGF levels [ 187 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…К естественным ингибиторам ангиогенеза относят следующие цитокины: фактор пигментного эпителия (PEDF), ангиостатин, эндостатин, TGF-β, IFN-γ, IFN-α и все тот же TNF-α, который при длительном воздействии на ЭК тормозит их пролиферацию и в итоге запускает их апоптоз [11,15,17]. Трансформирующий фактор β (TGF-β) -многофункциональная молекула, секретируемая многими клетками глаза: РПЭ, клетками Мюллера, ЭК, перицитами, фоторецепторами, астроцитами и выполняющая в глазу различные функции, касающиеся регуляции роста, пролиферации, миграции, апоптоза, нейропротекции, иммунной привилегированности глаза и многого другого [18]. Что касается неоангиогенеза, то TGF-β может выполнять как про-, так и антиангиогенную роль.…”
Section: четвертая панель -анализ содержания Tgf-β (B6)unclassified